Localization algorithms and strategies for wireless sensor networks - Mao, Guoqiang 1974-; Fidan, Baris; Gale Group (Hershey, Penn. Information Science Reference, 2009)
Provides comprehensive coverage of topics and fundamental theories underpinning measurement techniques and localization algorithms.
Introduction to wireless sensor network localization -- Measurements used in wireless sensor networks localization -- Localization algorithms and strategies for wireless sensor networks: monitoring and surveillance techniques for target tracking -- RF ranging methods and performance limits for sensor localization -- Calibration and measurement of signal strength for sensor localization -- Graph theoretic techniques in the analysis of uniquely localizable sensor networks -- Sequential localization with inaccurate measurements -- MDS-based localization -- Statistical location detection -- Theory and practice of signal strength-based localization in indoor environments -- On a class of localization algorithms using received signal strength -- Machine learning based localization -- Robust localization using identifying codes -- Evaluation of localization algorithms -- Accuracy bounds for wireless localization methods -- Experiences in data processing and Bayesian filtering applied to localization and tracking in wireless sensor networks -- A wireless mesh network platform for vehicle positioning and location tracking -- Beyond localization: communicating using virtual coordinates.
Electronic reproduction.
Keywords: Wireless sensor networks; Proximity detectors; Location problems (Programming); Electronic books